ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP CITRA MEREK PADA POLIKLINIK RS. HAJI MEDAN - rafika zahara lubis (Universitas Sumatera Utara, 2013)
The aim of the research was to know and analyze the influence of service quality to the brand image on the polyclinic Haji Hospital Medan. The primary data gathered by distributing questionnaires to the patients in order to make them the samples of the research. The research used descriptive analysis with multiple linear regression method. The population was 5521 outpatients of the hospital in 2011 (January until December 2011) and 83 of them used as the samples using Slovin formula with purposive sampling technique. The result of the research from significant simultaneous test (F-test) showed that simultaneously service quality which consisted of the dimension of variables of tangibles, reliability, responsiveness, assurance and empathy had significant influence to the brand image on the polyclinic Haji Hospital Medan. The result of partial test (T-test) showed that partially the variables of assurance, reliability, tangibles and empathy had the most positive and significant influence to the brand image on the polyclinic Haji Hospital Medan.Kata Kunci : bukti fisik, kehandalan, daya tanggap, jaminan, empati, citra merek.Keyword : tangibles, reliability, responsiveness, assurance, empathy and brand image.